(untitled) (FULafia Journal of Science and Technology, 2023)
Sweet potato (Ipomoea batatas (L) Lam) is a Staple – type food source on the Jos Plateau. A study was carried out to assay for its carbohydrate and soluble sugars at different harvest times. The improved varieties CIP4400168, Ex-Igbariam, Tanzania, TIS 8164 and TIS 87/0087 and local landraces, Jandankali I, Jandankali II, Jandankali III local varieties were collected from farmers on the Jos Plateau. These were planted within Jos, harvested after 4 and 6 months, processed into chips of 1 x 1 x 6mm dimension, dried in Air oven drier, milled and sieved to fine flours. One gram (1.0g) of the flour was dissolved in 50ml of distilled water, shaken in 250ml flask to extract its constituents, tested for carbohydrate and soluble sugars qualitatively and quantitatively for glucose, fructose, maltose and sucrose.